Супервізія в управлінні недержавними організаціями соціальної сфери: інституційний аналіз - Савка, Віктор Євгенович; Савка, Виктор Евгеньевич; Savka, Viktor Ie. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У роботі здійснено інституційний аналіз супервізії – однієї з технологій управління недержавними соціальними службами. Супервізія як управлінська технологія якісно відрізняється від традиційних підходів до управління, оскільки ґрунтується на принципах партнерства та взаємодопомоги. Це дає змогу максимально використовувати її можливості в громадських соціальних службах й обмежує застосування в державних, які є організаціями бюрократичного типу та, відповідно, ґрунтуються на принципах централізації й підпорядкування. We conducted an institutional analysis of supervision as one of the technologies for management of non-government social services. Supervision as management technology qualitatively differs from traditional management approaches, because it is based on partnership principles and mutual assistance. It allows use its features in public social services and limits in state, which are organizations of bureaucratic type and are based on the principles of centralization and subordination. Features of supervision allow to use it in the processes of internal management organization (supervision of workers and volunteers), and also in the management of customer service. Values bases of supervision fully consistent with the values of social work – one of the regulatory practices of social problems, usually practiced by non-state actors. Principles on which the supervision institution operates, creates preconditions for improving professional competence of social workers and at the same time – their civic qualities. This allows us to consider supervision as a technology with significant prospects for the use in other areas of professional and civic activities, but the actual social work.
Supervision in Management of non-Governmental Organizations in Social Areas: Institutional Analysis
Keywords: супервізія; соціальний інститут; інституційний аналіз; технологія управління; недержавні організації; supervision; social institution; institutional analysis; management technology; non-governmental organizations